Chromatin measurements reveal contributions of synthesis and decay to steady‐state mRNA levels - Sylvia C Tippmann; Robert Ivanek; Dimos Gaidatzis; Anne Schöler; Leslie Hoerner; Erik van Nimwegen; Peter F Stadler; Michael B Stadler; Dirk Schübeler (Molecular Systems Biology)
Abstract Messenger RNA levels in eukaryotes are controlled by multiple consecutive regulatory processes, which can be classified into two layers: primary transcriptional regulation at the chromosomal level and secondary, co‐ and post‐transcriptional regulation of the mRNA. To identify the individual contribution of these layers to steady‐state RNA levels requires separate quantification. Using mouse as a model organism, we show that chromatin features are sufficient to model RNA levels but with different sensitivities in dividing versus postmitotic cells. In both cases, chromatin‐derived transcription rates explain over 80% of the observed variance in measured RNA levels. Further inclusion of measurements of mRNA half‐life and microRNA expression data enabled the identification of a low quantitative contribution of RNA decay by either microRNA or general differential turnover to final mRNA levels. Together, this establishes a chromatin‐based quantitative model for the contribution of transcriptional and post‐transcriptional processes to steady‐state levels of messenger RNA.